The Lord and his Prayer - Wright, N. T. (Nicholas Thomas) (Grand Rapids, Mich. : W.B. Eerdmans ; Cincinnati, Ohio : Forward Movement Publications, 1997)
"Taking the Lord's Prayer clause by clause, Wright locates this prayer within the historical life and work of Jesus and allows the prayer's devotional application to grow out of its historical context."--Back cover.
"First published 1996 in Great Britain by Triangle, Society for Promoting Christian Knowledge"--T.p. verso.
"This book began life as a series of sermons preached in Lichfield Cathedral in Advent 1995"--Prologue.
Keywords: Lord's prayer -- Sermons; Church of England -- Sermons; Sermons, English